2015
DOI: 10.4028/www.scientific.net/amm.815.29
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Concrete by Using Palm Oil Fuel Ash (POFA) as a Cement Replacement Material

Abstract: Palm Oil Fuel Ash (POFA) is one of the solid waste in Malaysia and had trouble with the ash removal. Therefore, the use of waste oil palm ash can overcome the problem of solid waste. POFA is a pozzolanic material and it can act as a replacement of cement (OPC) to produce concrete with higher strength and low cost. POFA quality will increase as the range made up to a medium level of fineness in the size of 50 microns. POFA used to replace OPC is 0%, 10%, 30% and 50% by weight percent of OPC. POFA concrete compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Furthermore, spherical particles, instead of crushed ones, displayed a higher packing density at the wet state. It was found that FA has a very minimum variation to density due to moisture content comparing to natural soils [ 136 ]. FAs can be more insensitive to moisture content variation than other materials considering their high air void content.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Furthermore, spherical particles, instead of crushed ones, displayed a higher packing density at the wet state. It was found that FA has a very minimum variation to density due to moisture content comparing to natural soils [ 136 ]. FAs can be more insensitive to moisture content variation than other materials considering their high air void content.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Cement was replaced by fly ash with 5, 10, 15, 20, 25 and 30% and metakaolin by 5,10,15 and 20% with M40 grade of concrete for 7 and 28 days. Split tensile and compressive strength gives best results at 30% fly ash and 15% of metakaolin [21]. The concrete strength augment as the percentage of metakaolin content increase up to 15% of replacement with its cement weight.Metakaolin increases the strength of concrete in comparision with normal concrete [63].…”
Section: Strength Studiesmentioning
confidence: 99%
“…In concrete, metakaolin is used as replacement material. For every production of one ton of metakaolin leads to 175 kgs of CO 2 emission, which is very less when compared to Portland clinkers [21]. In Tables 1 and 2 physical and chemical properties of metakaolin are tabulated.…”
Section: Background Studymentioning
confidence: 99%
“…However, POFA could be utilized in the construction components as material as partial replacement of cement [18]. It might be used as cement substitution to obtain better strength than standard concrete due to the silica content in the POFA, which is higher than that of OPC [19]. It was discovered in 2004, Palm oil fuel ash, which had a significant quantity of silica and was crushed to a proper fineness, used to be a pozzolanic material that capable of producing high strength concrete with a 90-day strength of 100 MPa [20].…”
Section: Introductionmentioning
confidence: 99%